Importance of Maternal Diabetes on the Chronological Deregulation of the Intrauterine Development: An Experimental Study in Rat - Marcela Salazar García; Elba Reyes Maldonado; María Cristina Revilla Monsalve; Laura Villavicencio Guzmán; Alfonso Reyes López; Concepción Sánchez-Gómez (Journal of Diabetes Research)
We investigated whether maternal diabetes induced in rats using streptozotocin (STZ) on Day 5 of pregnancy affects the intrauterine developmental timeline. A total of 30 pregnant Sprague-Dawley diabetic rats (DRs) and 20 control rats (CRs) were used to obtain 21-day fetuses (F21) and newborn (NB) pups. Gestational age, weight, and body size were recorded as were the maxillofacial morphometry and morphohistological characteristics of the limbs. In DRs, pregnancy continued for ∼1.7 days, and delivery occurred 23 days postcoitus (DPC). In this group, the number of pups was lower, and 13% had maxillofacial defects. F21 in the DR group had lower weights and were smaller; moreover, the morphological characteristics of the maxillofacial structures, derived from the neural crest, were discordant with their chronological gestational age, resembling 18- to 19-day-old fetuses. These deficiencies were counterbalanced in NB pups. We conclude that hyperglycemia, which results from maternal diabetes and precedes embryo implantation, deregulates the intrauterine developmental timeline, restricts embryo-fetal growth, and primarily delays the remodeling and maturation of the structures derived from neural crest cells.